Advanced remote sensing - Liang, Shunlin; Li, Xiaowen, 1969-; Wang, Jindi (Boston : Academic Press, 2012)
'Advanced Remote Sensing is an application-based reference that provides a single source of mathematical concepts necessary for remote sensing data gathering and assimilation. It presents state-of-the-art techniques for estimating land surface variables from a variety of data types, including optical sensors such as RADAR and LIDAR. Scientists in a number of different fields including geography, geology, atmospheric science, environmental science, planetary science and ecology will have access to critically-important data extraction techniques and their virtually unlimited applications. While rigorous enough for the most experienced of scientists, the techniques are well designed and integrated, making the book's content intuitive, clearly presented, and practical in its implementation'--
Includes bibliographical references and index.
Keywords: Earth sciences -- Remote sensing; Environmental sciences -- Remote sensing; Remote sensing